113 Dual energy ct improves differentiation of coronary atherosclerotic plaque components compared to conventional single energy CT. (9th June 2011) - Obaid, D R; Calvert, P A; Rudd, J H F; Gopalan, D; Bennett, M R
Abstract : Introduction: Vulnerable plaques have a relatively high necrotic core area and low fibrous tissue content. Although CT can identify plaque components on the basis of their x-ray attenuation, there is significant overlap between their attenuation ranges, most crucially between necrotic core and fibrous plaque. Recently introduced dual energy CT (DECT) permits acquisition of 2 different energy data sets simultaneously, with the change in attenuation of plaque components to different energies depending upon their material composition. We therefore examined whether DECT was better than single energy CT in determining plaque components defined by virtual histology IVUS. Methods: 20 patients underwent DECT and 3-vessel VH-IVUS. CT data was obtained at peak voltages of 100 kV and 140 kV. 52 plaques were chosen with either homogenous fibrous plaque or confluent areas of calcified plaque or necrotic core as defined by VH-IVUS. VH-IVUS images were co-registered and orientated with the corresponding CT images using distance from coronary ostia and fiduciary markers (Abstract 113 figure 1 ). Multiple regions of interest (ROI) were placed within the plaque components or in lumen on cross sectional CT images pre-classified by VH-IVUS (Abstract 113 figure 1 ). ROI densities were measured (in Hounsfield Units) and assigned to the plaque component. A dual energy index (DEI) was created for each component, defined as the ratio of the difference in attenuation at 2 different energies / sum of attenuation with 1000 added to each attenuation value to avoid negatives. Results: Attenuation values for 1088 ROIs were measured from 70 paired data sets at 100 kV and 140 kV creating 70 DEIs (12 necrotic core, 11 fibrous plaque, 29 calcified plaques and 18 lumen). Values obtained using a single energy data set showed good differentiation between calcified plaque and all others (p<0.05), but considerable overlap between necrotic core and fibrous plaque (p=ns) (Abstract 113 figure 2A ) (Abstract 113 table 1 ). In DECT, lumen (iodinated contrast) showed the greatest change in attenuation and hence had the highest DEI. Necrotic core had the lowest DEI and could be distinguished from all other components (p<000.1) Importantly, in contrast to the single energy data, DEI derived from both energy data sets permitted resolution of necrotic core and fibrous plaque without overlap (Abstract 113 figure 2B ). Conclusions: The additional attenuation data provided by DECT improves the differentiation of plaque components when compared to conventional single energy CT. In particular, DECT may allow better differentiation of necrotic core and fibrous plaque, a weakness of conventional cardiac CT, allowing for more accurate non-invasive identification of vulnerable plaques.